Limites e controle do negociado sobre o legislado em face do princípio da intervenção mínima na autonomia coletiva: efeitos da Lei nº 13.467 DE 2017 - Gurgel, Christianne Moreira Moraes (2020)
According to the legislative changes made by Law No. 13,467, of July 13, 2017, they impacted several institutes of Collective Labor Law. In the midst of these important changes, the labor reform required that, in the examination of the collective agreement or convention, the Labor Court must guide its performance by the mandatory mandatory autonomy of the collective will, restricting its appreciation to the essential elements of the general legal business in Civil Code. The present study proposes a careful and reasoned analysis of the limits and control of the overlapping of negotiations in the face of the legislature, considering the effects caused by the reform with the imposition of compliance with the principle of state intervention. To this end, the study seeks to provide an overview of the most significant legislative changes in Union Law, moving on to the main aspects of collective work autonomy and collective bargaining, placing the reader in the great appreciation of these institutes in the scope of domestic and international law. Finally, the central objective of the study is to examine the institutes, principles and rules of the Legal Order that seek to respond to the limits and control of the negotiated over the legislature, in view of the principle of minimum State intervention